The Effect of Tax Reform for Acceleration and Inclusion (TRAIN) Law on the Operational Performance of Food Franchises and Stalls in Cabugao, Ilocos Sur - Aira Mae S Socias; Jhazpher A Raquepo; JIEZLE MAE I. REMOLACIO; Marc Anthony S Saupan; Laureen T Savellano (Applied Quantitative Analysis, 2023)
This research aims to investigate the effect of the Tax Reform for Acceleration and Inclusion Law on small food businesses, specifically franchises and food stalls, in Cabugao, Ilocos Sur. The study focuses on businesses that have been in operation for at least five years, as their longer existence allows for a comprehensive understanding of the effects of the Tax Reform for Acceleration and Inclusion Law on their operations. The researchers developed questionnaires to determine the level of operating performance and the effectiveness of the Tax Reform for Acceleration and Inclusion Law. The majority of respondents aged 40-49 are college graduates who have attended 1-3 seminars. Most small business owners have been in operation for over 10 years and have hired 1-3 employees, usually family members. The study found that small business owners do not believe the tax reform has a positive impact on income generation, and that the increase in purchasing power has not significantly affected their businesses. However, businesses use incentives to optimize their income and have lower personal income tax rates. The increase in operating costs does not lead to cost-saving measures, and marketing expenses do not contribute to profitability. Lastly, in 2018 and 2019, small business owners reported sales above P300,000 and had expenses below P50,000. Over the subsequent years, the pattern varies. Notably, in 2020 and 2021, small business owners reported sales below P50,000 and expenses also below P50,000. In 2022, reported sales were between P50,000 and P100,000, and the expenses were below P50,000. Hence, the business's operating performance was not affected by the implementation of the Tax Reform for Acceleration and Inclusion Law.